1967
DOI: 10.1093/bja/39.6.485
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Radiological Visualization of the Catheters Placed in the Epidural Space

Abstract: Radiographs of the position of the epidural catheter were taken in each of 90 patients in whom this form of analgesia was employed for surgery. Radiopaque dye was injected through the catheter. In 33 patients the average length of catheter threaded into the epidural space was 20 cm; the desired cephalad direction was followed in 16. When the average length of catheter inserted was 12.5 cm the tip followed the cephalad direction in 27 of 57 patients. Straight, curled up, and winding patterns were observed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 1 publication
2
23
1
Order By: Relevance
“…Sixteen of these were found to have emerged through the intervertebral foramina. Only half of these patients experienced paraesthesia during catheter insertion, Sanchez et al 3 performed a similar radiological study in 1967 with 90 catheters inserted to distances ranging from…”
Section: Discussionmentioning
confidence: 98%
“…Sixteen of these were found to have emerged through the intervertebral foramina. Only half of these patients experienced paraesthesia during catheter insertion, Sanchez et al 3 performed a similar radiological study in 1967 with 90 catheters inserted to distances ranging from…”
Section: Discussionmentioning
confidence: 98%
“…Lim et al (20) found that the catheter tip could be advanced without coiling for 4cm or less in only 13% of cases. Hogan (21) found that lateral catheter deviation is a more common cause of asymmetric block than anatomic barriers to the spread of the local anesthetic solution Using radiography, Sanchez et al (22) showed that the intended catheter placement was often not achieved. When epidural anesthesia is incomplete, additional injections or catheter manipulation may provide reliable surgical anesthesia, suggesting suboptimal positioning of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…The coiling length was similar irrespective of the cephalad (1-5.5 cm) or caudal direction (1.5-8 cm) of the needle. Bends were noted on the removed catheters, suggesting that after being advanced a short distance into the epidural space, the catheters became coiled within the epidural space [12,15,16]. A catheter bends when the tip confronts the dura mater, blood vessels, connective tissue, and neural structures that may hinder its advancement [4].…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between what is felt and what is observed can assist in gauging the behavior of a catheter when it is inserted at different lengths inside the epidural space. Investigators have used radiological methods to study the behavior of a catheter inside the epidural space, but it is not feasible to use such methods to determine the point of intravascular placement [12]. This study was designed to investigate where the resistance was felt during the advancing of a catheter into the epidural space and whether the length of catheter advanced in the epidural space affected the incidence of catheter migration.…”
Section: Introductionmentioning
confidence: 99%